2018
DOI: 10.1186/s12885-018-4670-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pre-transplant minimal residual disease on prognosis after Allo-SCT for patients with acute lymphoblastic leukemia: systematic review and meta-analysis

Abstract: BackgroundThis meta-analysis was performed to explore the impact of minimal residual disease (MRD) prior to transplantation on the prognosis for patients with acute lymphoblastic leukemia (ALL).MethodsA systematic search of PubMed, Embase, and the Cochrane Library was conducted for relevant studies from database inception to March 2016. A total of 21 studies were included.ResultsPatients with positive MRD prior to allogeneic stem cell transplantation (allo-SCT) had a significantly higher rate of relapse compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…LFS at 3 years was 27% in MRD + and 49% in MRD − patients ( P = 0.05). Furthermore, a recently published meta‐analysis of 21 studies laid further credence to the concept of pre‐MRD by showing pre‐MRD status to be independently associated with higher CIR and lower LFS, and OS, irrespective of the detection method . Taking the results reported by others and us together, the marked deleterious prognostic role played by a positive pre‐MRD suggests that strategies should be adopted to make the MRD negative, which might improve transplant outcomes.…”
Section: Discussionmentioning
confidence: 67%
“…LFS at 3 years was 27% in MRD + and 49% in MRD − patients ( P = 0.05). Furthermore, a recently published meta‐analysis of 21 studies laid further credence to the concept of pre‐MRD by showing pre‐MRD status to be independently associated with higher CIR and lower LFS, and OS, irrespective of the detection method . Taking the results reported by others and us together, the marked deleterious prognostic role played by a positive pre‐MRD suggests that strategies should be adopted to make the MRD negative, which might improve transplant outcomes.…”
Section: Discussionmentioning
confidence: 67%
“…A number of previous studies confirm a negative effect of positive pre-MRD in patients undergoing allo-SCT (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). In a recent meta-analysis of 21 studies, Shen et al (51) found that in HLA-matched allo-SCT settings, positive pre-MRD was related to higher CIR (HR, 3.26; P < 0.05) as well as lower relapsefree survival (HR, 2.53; P < 0.05), LFS (HR, 4.77; P < 0.05), and OS (HR, 1.98; P < 0.05). In the current study, we found that Ph-positive ALL cases with positive pre-MRD in the MSDT group experienced higher CIR and lower OS and LFS.…”
Section: Discussionmentioning
confidence: 90%
“…The prognostic value of MRD measured prior to allogeneic hematopoietic cell transplantation (HCT) on its outcomes was first observed in small retrospective [2, 3] and prospective [4] studies of children and adolescents and later also in adults [57], and confirmed in a recent meta-analysis [8]. However, it remains unclear if or to what extent the choice of conditioning regimen impacts on this.…”
Section: Introductionmentioning
confidence: 99%